Widespread occurrence and relevance of phosphate storage in foraminifera - Nicolaas Glock; Julien Richirt; Christian Woehle; Christopher Algar; Maria Armstrong; Daniela Eichner; Hanna Firrincieli; Akiko Makabe; Anjaly Govindankutty Menon; Yoshiyuki Ishitani; Thomas Hackl; Raphaël Hubert-Huard; et al. (Nature, 2025)
Abstract Foraminifera are ubiquitous marine protists that intracellularly accumulate phosphate1, an important macronutrient in marine ecosystems and in fertilizer potentially leaked into the ocean. Intracellular phosphate concentrations can be 100–1,000 times higher than in the surrounding water1. Here we show that phosphate storage in foraminifera is widespread, from tidal flats to the deep sea. The total amount of intracellular phosphate stored in the benthic foraminifer Ammonia confertitesta in the Wadden Sea during a bloom is as high as around 5% of the annual consumption of phosphorus (P) fertilizer in Germany. Budget calculations for the Southern North Sea and the Peruvian Oxygen Minimum Zone indicate that benthic foraminifera may buffer riverine P runoff for approximately 37 days at the Southern North Sea and for about 21 days at the Peruvian margin. This indicates that these organisms are probably relevant for marine P cycling—they potentially buffer anthropogenic eutrophication in coastal environments. Phosphate is stored as polyphosphate in cell organelles that are potentially acidocalcisomes. Their metabolic functions can range from regulation of osmotic pressure and intracellular pH to calcium and energy storage. In addition, storage of energetic P compounds, such as creatine phosphate and polyphosphate, is probably an adaptation of foraminifera to O2 depletion.